Operational parameters affecting pneumatic paddy seeds - Abdulkadir, Tukur Daiyabu; Mahadi @ Othman, Muhammad Razif; Wayayok, Aimrun; Mohd Kassim, Muhamad Saufi (International Commission of Agricultural and Biosystems Engineering, 2019)
This study was carried out to determine the critical operational parameters for pneumatic handling of MR219 paddy seeds, with emphasis to seeding of system of rice intensification (SRI) seedling tray. The relevant physical and aerodynamic properties of MR219 seeds were studied. Twenty nozzle designs were developed based on the physical properties. A suitable operational vacuum pressure for single paddy seed picking was determined from established models based on one thousand kernel mass M1000, true density, sphericity and projected area of MR219 paddy seed. The performances of the twenty nozzle designs were evaluated experimentally using an automated platform consisting of screw mechanism, vacuum manifold, solenoid valve, vacuum pump and Atmel microcontroller. The amount of vacuum suction required for single seed picking derived from the established models was found to be 18.30 to 29.15 mbar. However, the amount of vacuum suction was optimized experimentally where 25 to 30 mbar was found to be suitable vacuum pressure for single seeding of MR219 paddy seed using 1 mm to 1.5 mm seed-hole diameter. The highest performance of 96.7% single seeding, 3.3% multiple seeding, and 0% miss seeding was achieved using nozzle with 1 mm seed hole diameter at 30 mbar vacuum pressure.